2013
DOI: 10.4049/jimmunol.1202975
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional RORγt+ T Cells Drive Hepatic Ischemia Reperfusion Injury

Abstract: An emerging body of evidence suggests a pivotal role of CD3+ T cells in mediating early ischemia reperfusion injury (IRI). However, the precise phenotype of T cells involved and the mechanisms underlying such T cell–mediated immune responses in IRI, as well as their clinical relevance, are poorly understood. In this study, we investigated early immunological events in a model of partial warm hepatic IRI in genetically targeted mice to study the precise pathomechanistic role of RORγt+ T cells. We found that unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…All animals were euthanized 24 h following transient ischaemia/reperfusion. The surgical procedure was performed as described elsewhere 44 . In brief, C57BL/6J mice were narcotized with xylazine/ketamine and shaved at their front.…”
Section: Methodsmentioning
confidence: 99%
“…All animals were euthanized 24 h following transient ischaemia/reperfusion. The surgical procedure was performed as described elsewhere 44 . In brief, C57BL/6J mice were narcotized with xylazine/ketamine and shaved at their front.…”
Section: Methodsmentioning
confidence: 99%
“…Th17 cells contribute to the inflammatory response by mediating the recruitment of macrophages and neutrophils to injured tissues 7 . Moreover, RORγt-expressing (RORγt + ) T cells are the main source of Th17-producing cells during the early phase of liver IRI 8 . We previously demonstrated that RORγt/IL-17A + -expressing T cells played a crucial role in mediating hepatic IRI 9 .…”
Section: Introductionmentioning
confidence: 99%
“…hepatocytes by DN T cells. CD3+ DN T cells also have been shown to play a role in amplifying early ischemia reperfusion injury (Eggenhofer et al , 2013). The ability of DN T cells to respond to ischemic or APAP induced liver injury and amplify the course of hepatotoxicity that evolves over the first 3–24 hours suggests that these T cells have insufficient time to develop adaptive immune responses to non-self antigens and thus are more likely to be responding via innate immune response mechanisms or TCR responses to auto- or neo-antigens exposed or produced as part of hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%